QUANTITATIVENESS IN UZBEK AND KAZAKH FOLK PROVERBS (Scientific journal of the Fergana State University, 2026)
In the contemporary Turkic world, exploring the cultural and lifestyle similarities among fraternal nations through proverbs holds both scholarly and practical significance. This article presents a comparative analysis of Uzbek and Kazakh proverbs with quantitative features. The introduction outlines the relevance of the topic, while the literature review and methodology sections list the sources related to the subject, highlighting the most essential ones as the methodological foundation. The “Results and Discussion” section shows that numerical and quantitative expressions in proverbs serve various communicative and moral purposes. In particular, proverbs containing numbers denoting human age are examined in both Uzbek and Kazakh, emphasizing the instructive moral insights they convey. The conclusion summarizes the key findings obtained throughout the study, followed by the list of references used.